The first triple-decker complex with a carbenium center, (CpCo([mu]-C3B2Me5)RuC5Me4CH2)+: synthesis, reactivity, X-ray structure, and bonding - Muratov, Dmitry V.; Siebert, Walter (Chemistry - a European journal, 2017)
The first derivative of the methylium cation with the triple-decker substituent, [CpCo(C3B2Me5)RuC5Me4CH2]PF6 (2PF6), was synthesized from the reaction of the triple-decker complex CpCo(C3B2Me5)RuCp* (1) with the salt of the trityl cation [CPh3]+. The X-ray crystal structure of 2PF6 reveals that the methylium carbon is bound to the ruthenium with Ru−C bond length of 2.259 Å and corresponds to the description of its structure as η6-fulvene-ruthenium. Reactions of 2PF6 with nucleophiles OH−, Ph3P, Et3N led to the corresponding derivatives of 1 in high yields. Aromatic amines PhNEt2 and 4-MeC6H4NH2 react with 2PF6 to give the electrophilic aromatic substitution products quantitatively. Chemical reduction of 2PF6 with Zn powder in tetrahydrofuran leads to the formation of the bis(triple-decker) derivative (CpCo(C3B2Me5)RuC5Me4CH2)2 (10) with a CH2CH2-bridge. The structures of complexes 4, 7-10 were determined by X-ray diffraction. Density functional calculations support the crystallographically determined geometry of 2 and allow rationalization of some characteristics of its structure, spectroscopy, and reactivity.